2014
DOI: 10.1093/restud/rdu023
|View full text |Cite
|
Sign up to set email alerts
|

Demand Reduction and Inefficiency in Multi-Unit Auctions

Abstract: Auctions often involve the sale of many related goods: Treasury, spectrum and electricity auctions are examples. In multi-unit auctions, a bid for one unit may affect payments for other units won, giving rise to an incentive to shade bids differently across units. We establish that such differential bid shading results generically in ex post inefficient allocations in the uniform-price and pay-as-bid auctions. We also show that, in general, the efficiency and revenue rankings for the two formats are ambiguous.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
274
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(296 citation statements)
references
References 46 publications
(57 reference statements)
5
274
0
5
Order By: Relevance
“…Instead, they bid on packages that could possibly form a feasible allocation under certain assumptions about the demands of competitors. This can also be considered a form of strategic demand reduction, a phenomenon that has received much attention in the literature on multi-unit auctions (Ausubel and Cramton, 2002;Weber, 1997).…”
Section: Searching For a Focal Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they bid on packages that could possibly form a feasible allocation under certain assumptions about the demands of competitors. This can also be considered a form of strategic demand reduction, a phenomenon that has received much attention in the literature on multi-unit auctions (Ausubel and Cramton, 2002;Weber, 1997).…”
Section: Searching For a Focal Pointmentioning
confidence: 99%
“…Gul and Stacchetti (1999) showed that even if the substitutes condition is satisfied, then ascending and linear-price auctions such as the SMRA cannot implement the VCG outcome. In contrast, demand reduction has widely been observed in the field and analyzed game-theoretically (Ausubel and Cramton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…5 With n = 2 agents the non-existence of equilibria has long been recognized in the literature when marginal utility is decreasing (e.g. Kyle (1989) from Ausubel et al (2014), Du and Zhu (2016)). …”
Section: Frameworkmentioning
confidence: 99%
“…This strategic behavior is commonly known as "demand-reduction" from standard multi-unit auctions that sell (here trade) one good, given agents have demand for multiple units (see Ausubel et al (2014)). It carries over to the case of multiple goods where the true demand is multi -(here two -) dimensional.…”
Section: Frameworkmentioning
confidence: 99%
“…If, at round n ϩ 1, bidder j bids straightforwardly, then, regardless of the bids made by others, j 's assignment S ′ j at the end of round n ϩ 1 satisfies S ′ j ∈X j (p j ′), where p j ′ is j 's personalized price at the end of round n ϩ 1. Moreover, j 's tentative profit after any round-what it would earn if the auction were terminated after 9 Ausubel and Cramton (1996) argue that an incentive of this sort is unavoidable in a wide class of auctions, including all those that establish uniform prices for identical objects.…”
Section: Auctions and Tatonnement Theorymentioning
confidence: 99%